THE COUNTER RADICALISM AND INTOLERANCE STRATEGY OF NAHDLATUL ULAMA HIGHER EDUCATION IN INDONESIA - Abdul Aziz; Imam Yahya; Fatah Syukur; Mohamad Fathurohman (Al-A'raf: Jurnal Pemikiran Islam dan Filsafat)
This study aims to investigate the role of Nahdlatul Ulama Higher Education (PTNU) in Purworejo, Central Java, in relation to counter-extremism and intolerance in Indonesia. This is a qualitative study that focuses on narrative analysis. The data is gathered from various documents and news articles. The data is analyzed using Ernest Gellner's idea of civil society. The results show that PTNU has a significant role in Indonesia’s religious moderation movement through two main strategies. First, the institution's policies, which are aligned with national principles, serve to strengthen moderate ideologies. Second, as part of its tri-dharma commitment, PTNU integrates scientific, Islamic, and Indonesian principles into its curriculum and activities. Thus, this strategy integrates religious moderation systematically, with broad ramifications for academia and society. PTNU is known for combining academic excellence with holistic ideals, making it a center for religious moderation amid Indonesia's multifaceted extremism and intolerance. This study provides new insights on PTNU's role in the religious moderation movement and could inform both domestic and worldwide actions.